Patients' perceptions of the quality of nursing services - Ali Reza Yusefi; Shakiba Rohani Sarvestani; Zahra Kavosi; Jamshid Bahmaei; Morteza Mortazavi Mehrizi; Gholamhossein Mehralian (BMC, 2022)
Abstract Introduction The quality of nursing services is one of the main factors accelerating patients' recovery. The present study aimed to examine patients' perceptions of the quality of nursing services in the teaching hospitals of Iran. Methods This cross-sectional research was a descriptive-analytical study conducted in 2021, in which 1067 patients were selected as the research sample. The Qualipak nursing quality questionnaire (QUALPAC) was used to collect the required data. Data were analyzed using t-test, ANOVA, and Pearson correlation coefficient using SPSS software version 23. Results From the patients' perspective, the mean and standard deviation of the quality of nursing services was 191.47 ± 19.51. Among the quality dimensions, all services quality: psychosocial (91.34 ± 9.34), physical (65.72 ± 10.18), and communication (34.41 ± 6.21) were placed at the moderate level. A significant association was found between patients' age and nursing service quality. The perceived nursing service quality was subject to sex (P = 0.01, t = 1.921) and place of residence (P = 0.02, t = 1.873). Conclusion According to the findings, the quality of nurses 'care was "moderate" from the patients' perspectives. Planning is recommended to reinforce and promote the quality of nursing services.